Comparison of the Manuscripts of the Book As-Sunan As-Sughra Wa Al-Kubra Lil Baihaqi: Analysis of the Compilation Methodology - Dede Muhamad Wahyudin; Hanhan Suherlan; Rizzaldy Satria Wiwaha; Dadah; Mulyana Mulyana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the manuscripts of As-Sunan as-Sughrā and As-Sunan al-Kubrā by al-Imām al-Bayhaqī (d. 458 H), two monumental works in the treasury of Islamic hadith that represent the peak of the development of codification and systematization of hadith-based law in the 5th century H. The study focuses on philological, methodological, and epistemological aspects, including the structure of the compilation, reference sources, and the principles of sanad and matan criticism applied by al-Bayhaqi. The research method used is qualitative through library research, with an approach of classical and comparative manuscript analysis of various printed editions and available digital manuscripts. The results of the study indicate that As-Sunan al-Kubrā functions as an encyclopedia of hadith law with a comprehensive thematic systematics, while As-Sunan as-Sughrā is a concise and selective version compiled for the practical needs of fiqh. Methodologically, al-Bayhaqi presents an integration between the approaches of hadith scholars and fiqh scholars (jam‘ bayna al-madrasatayn), making his work an important bridge between the traditions of riwayah and dirayah. Manuscript analysis also reveals several textual variants and editorial differences that have implications for legal understanding in Shafi‘i fiqh literature. Thus, this study emphasizes the importance of philological studies of al-Bayhaqi’s work to strengthen understanding of the evolution of hadith epistemology and classical Islamic law.